Integration of Health Education Technology to Improve Mothers' Understanding of Toddler Nutrition in the Ciputat Timur Community Health Center Area, South Tangerang - Wintarti, Wahyunita Gani (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to analyze the effectiveness of integrating health education media in improving maternal knowledge regarding toddler nutrition in the working area of the Ciputat Timur Community Health Center, South Tangerang.Methodology: A quantitative study with a quasi-experimental design using a non-equivalent control group approach was conducted. The study involved 36 mothers of toddlers, consisting of 9 mothers of underweight toddlers (intervention group) and 27 mothers of well-nourished toddlers (control group). Data were collected using a structured questionnaire measuring maternal knowledge before and after the educational intervention. The intervention included health education using flipchart media and video-based educational materials, while the control group received education using flipchart media only. Main Findings: The results showed a significant improvement in maternal knowledge after the educational intervention. In the underweight toddler group, the median knowledge score increased from 65.00 to 80.00 (p = 0.007). In the well-nourished toddler group, the median knowledge score increased from 70.00 to 80.00 (p < 0.001). Furthermore, the proportion of mothers with knowledge scores above 70 increased from 0% to 66.7% in the underweight group and from 48.1% to 85.2% in the well-nourished group.Novelty/Originality of this study: The novelty of this study lies in the integration of multiple health education media, including flipcharts and video-based learning, within a community-based nutrition education intervention at the primary health care level, providing a more interactive and effective approach to improving maternal nutrition literacy.